(untitled) (El-Wahat Journal for Research and Studies, 2023)
Abstract: The current study aims to reveal the level of social responsibility among the employees of the Setram Ouargla Corporation. To achieve the objective of the study, the social responsibility scale by "Maysoun Musharraf" was applied to a sample of 100 employees who were chosen randomly, using the descriptive approach .The study also focused on finding out the differences in social responsibility according to the age, educational level and occupation, where the results revealed that the level of social responsibility among the study sample is high and that there are no statistically significant differences due to the variable of age and educational level and that there are statistically significant differences attributed to the occupation variable. Keywords: social responsibility, Setram employees.